2021
DOI: 10.1158/1078-0432.ccr-20-1163
|View full text |Cite
|
Sign up to set email alerts
|

Genome and Transcriptome Biomarkers of Response to Immune Checkpoint Inhibitors in Advanced Solid Tumors

Abstract: Clinical response to immune checkpoint inhibitors (ICIs) varies significantly and the majority of studies into their effectiveness are focused on primary tumours of single histologies. This retrospective study utilises whole genome and transcriptome analysis (WGTA) to examine a pan-cancer cohort of advanced and previously treated patients which are currently underrepresented in the field, yet encompass a large proportion of cancer patients routinely seen in clinics. Our results reveal that tumour mutation burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 53 publications
2
73
1
Order By: Relevance
“…IL-34 and M-CSF can induce macrophages to differentiate into the M2 type, leading to immune suppression mediated by M2 macrophages (37). It is worth noting that M2 macrophages are generally considered cancer-promoting, which seems to differ from our results, and the reasons for this need to be explored (38,39). IL-34 is related to PD-L1 expression and the PD-1 signaling pathway.…”
Section: Discussioncontrasting
confidence: 56%
“…IL-34 and M-CSF can induce macrophages to differentiate into the M2 type, leading to immune suppression mediated by M2 macrophages (37). It is worth noting that M2 macrophages are generally considered cancer-promoting, which seems to differ from our results, and the reasons for this need to be explored (38,39). IL-34 is related to PD-L1 expression and the PD-1 signaling pathway.…”
Section: Discussioncontrasting
confidence: 56%
“…Another study, investigating renal cell carcinoma tissues from patients treated with a combination of anti-PD-L1 and anti-VEGF-A mAbs (atezolizumab and bevacizumab, respectively) revealed a correlation between a high T effector gene signature and an improved overall response rate and progression-free survival, while a high myeloid inflammation gene signature was associated with a reduced progression-free survival [ 28 ]. Furthermore, in advanced solid tumors the M1/M2 macrophage ratio score together with the tumor mutational burden and CD8+ scores were all predictors of response to ICIs [ 29 ].…”
Section: From Circulating Monocytes To Tumor-associated Macrophagementioning
confidence: 99%
“…After abstract review, we identified 34 articles for full manuscript review and 28 of these articles were excluded for the reasons delineated in Figure 1. Finally, nine studies from six articles (23,(28)(29)(30)(31)(32) were included in the final meta-analysis (Table 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%